Automatic speech analysis for the assessment of patients with predementia and Alzheimer's disease - Alexandra König; Aharon Satt; Alexander Sorin; Ron Hoory; Orith Toledo‐Ronen; Alexandre Derreumaux; Valeria Manera; Frans Verhey; Pauline Aalten; Phillipe H. Robert; Renaud David (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2015)
Abstract Background To evaluate the interest of using automatic speech analyses for the assessment of mild cognitive impairment (MCI) and early‐stage Alzheimer's disease (AD). Methods Healthy elderly control (HC) subjects and patients with MCI or AD were recorded while performing several short cognitive vocal tasks. The voice recordings were processed, and the first vocal markers were extracted using speech signal processing techniques. Second, the vocal markers were tested to assess their “power” to distinguish among HC, MCI, and AD. The second step included training automatic classifiers for detecting MCI and AD, using machine learning methods and testing the detection accuracy. Results The classification accuracy of automatic audio analyses were as follows: between HCs and those with MCI, 79% ± 5%; between HCs and those with AD, 87% ± 3%; and between those with MCI and those with AD, 80% ± 5%, demonstrating its assessment utility. Conclusion Automatic speech analyses could be an additional objective assessment tool for elderly with cognitive decline.